Adequacy of Dietary Intake of Vitamin D in Stable HD Patients: Are they meeting their needs - Sara Mahdavi; Catherine Amara; Tabo Sikaneta (The Korean Society of Nephrology, 2012)
Hypovitaminosis D is associated with reduced survival, increased cardiovascular events, and impaired bone-mineral balance in dialysis. The KDOQI guidelines do not have specific recommendations regarding vitamin D (VitD) intake in dialysis patients. The purpose of this study was to determine whether stable prevalent hemodialysis (HD) patients, for whom standard clinical dietary restrictions had been recommended, were able to meet their Recommended Daily Allowance (RDA) for VitD. An observational study was conducted to examine serum 25-OHD levels in relation to 3-day diet analysis, supplementation, anthropometrics and nutritional status (using Malnutrition Inflammation Score (MIS)) in 81 HD patients. Sixty-nine completed 3-day dietary intake records (1 dialysis day, 1 non-dialysis day, 1 weekend-non-dialysis day). Mean dietary VitD intake of the group was 2.5 μg/day SD±3.6, which is less than 15% of RDA of ∼17 μg/day. Only 2 out of 69 subjects (3%) met the RDA for VitD with mean intakes of 20.8±2.6 μg/day that corresponded with mean serum 25OHD of 43.5±17.6 nmol/L. Mean serum 25OHD levels for the group were 42.4 ±23.1 nmol/L, with 19 classified as deficient (28% <27.5 nmol/L), 43 insufficient (62%=27.5-75 nmol/L) and only 7 sufficient (10% >75nmol/L) in terms of 25OHD levels. 20 of the 69 (29%) took a VitD supplement and had significantly higher serum 25OHD than ones who did not take any (53.7±17.3 nmol/L vs 38.7±22.4 nmol/L, p-value=0.013). Multiple regression analysis revealed dietary calcium (p=0.001), and dietary protein (p=0.006) were positively related and HD-vintage (p=0.037), inversely related to dietary VitD whereas total kilocalories, dietary phosphate, MIS and dry body mass did not relate to it. Thus, inadequate intake of VitD is a common (97%) and modifiable risk factor for hypovitaminosis D in HD patietns. Factors affecting reduced intake of VitD in our patients included dietary protein and calcium but not dietary phosphorous. VitD levels were low even in the face of adequate VitD intake through supplementation and/or dietary sources, and would need monitoring if target levels are to be met by the renal dietitians and nephrologists.